2012
DOI: 10.1590/s1516-14392012005000093
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen absorption/desorption properties in the TiCrV based alloys

Abstract: Three different Ti-based alloys with bcc structure and Laves phase were studied. The TiCr 1.1 V 0.9 , TiCr 1.1 V 0.45 Nb 0.45 and TiCr 1.1 V 0.9 + 4%Zr 7 Ni 10 alloys were melted in arc furnace under argon atmosphere. The hydrogen absorption capacity was measured by using aparatus type Sievert's. Crystal structures, and the lattice parameters were determined by using X-ray diffraction, XRD. Microestructural analysis was performed by scanning electron microscope, SEM and electron dispersive X-ray, EDS. The hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The positive impact of additives such as Zr 7 Ni 10 on hydrogen sorption and kinetic characteristics of ternary alloys was reported for the first time in [12]. It was suggested that the benefit of the additive should result from hydrogen permeation through a first oxide layer of the C14 Laves phase formed on the TiCr 1.1 V 0.9 + 4 mol.% Zr 7 Ni 10 composite alloy [13]. The H-permeation allows forming cracks along the grain boundaries and exposes new surfaces to hydrogen, which can penetrate the b.c.c.…”
Section: Discussionmentioning
confidence: 97%
“…The positive impact of additives such as Zr 7 Ni 10 on hydrogen sorption and kinetic characteristics of ternary alloys was reported for the first time in [12]. It was suggested that the benefit of the additive should result from hydrogen permeation through a first oxide layer of the C14 Laves phase formed on the TiCr 1.1 V 0.9 + 4 mol.% Zr 7 Ni 10 composite alloy [13]. The H-permeation allows forming cracks along the grain boundaries and exposes new surfaces to hydrogen, which can penetrate the b.c.c.…”
Section: Discussionmentioning
confidence: 97%
“…The storage and distribution of hydrogen is a critical aspect of the industrialization of hydrogen energy [ 2 , 3 , 4 , 5 ]. Owing to their ability to store hydrogen safely, their comparatively large hydrogen storage capacity, and their relatively low hydrogen pressure, hydrogen storage alloys have the potential to displace existing hydrogen storage systems such as high-pressure gas storage and cryogenic liquid storage [ 2 , 6 , 7 , 8 , 9 ]. The Ti-V solid solution has a potential hydrogen storage content of 3.7 wt%, which is higher than that of AB 5 and AB 2 alloys, and it has milder hydrogen-absorption conditions than Mg-based alloys [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been taken to overcome this drawback. These include heat treatment [12], addition of Zr 7 Ni 10 [12][13][14][15][16], or Zr [17,18] and by element substitution [19,20]. Another approach was made by Edalati K. et al [21] who used high-pressure torsion to induce microstructural modification and so enhancing hydrogen storage properties of Ti-V BCC alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Shashikala et al [19] noticed that Zr is the element responsible for producing the secondary phase that ensures a rapid reaction with hydrogen and observed that hydrogen absorption capacity was decreased as the Zr content increased due to a greater fraction of Laves phase. In addition, Martinez and Santos found that TiV 0.9 Cr 1.1 alloy with addition of 4 wt % of Zr 7 Ni 10 showed fast hydrogenation kinetics and high capacity (3.6 wt %) [14]. Lately, Bellon et al showed that by substituting Zr for V in the alloy TiCrV resulted in a two-phase structure made up of a main BCC structure and a less abundant cubic-type Laves phase C15.…”
Section: Introductionmentioning
confidence: 99%